Sociological analysis to the communicative technological system - Zenkoufi, Fouzia Mahmoud; Korzet, Najima AbdElkader (Journal of Humanities & Social Sciences, 2023)
We live in an era of communication based on the use of technology as a means for developing human relationships. The rapid and amazing development in communication technology has led to the production of modern means of social communication that have worked to develop the human factor through the diversity of its programs and its constant renewal. In this way, information and communication technology has contributed to the promotion of human, economic, social and cultural development. It has become so widespread that it has transcended geographical and political boundaries. To this end, the revolutions in communication technology and information technology are inseparable, as they are indispensable indicators of rapid technological progress, combined to the digital system that works on developing communication systems and linking communication networks with information networks. Accordingly, we are trying to reveal in our topic the evolutionary implications of the communication system, and how the cultural expansion of this technology use has been extended to improve the communication process, all through a sociological analytical vision that shows us how to switch from the communication process to the new communication system.